2001
DOI: 10.1046/j.1469-7580.2001.19810047.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate moieties of the interstitial and glandular tissues of the amphibian Pleurodeles waltl testis shown by lectin histochemistry

Abstract: The amphibian testis is a useful model because of its zonal organisation in lobules, distributed along the cephalocaudal axis, each containing a unique germ cell type. Sperm empty lobules form the so‐called glandular tissue at the posterior region of the gonad. Androgen production is limited to the cells of the interstitial tissue surrounding lobules with spermatozoa bundles and to the cells of the glandular tissue. In this work, we have studied the distribution of terminal carbohydrate moieties of N‐ and O‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…), including amphibians (Sáez et al. , ,b, ,b, ), but no reports exist about the identification of NeuAc and GlcNAc in Xenopus testis. From our data, it could be concluded that terminal GlcNAc is more abundant than sialic acid, because labelling with GlcNAc‐binding lectins was generally stronger than labelling with NeuAc‐binding lectins.…”
Section: Discussionmentioning
confidence: 99%
“…), including amphibians (Sáez et al. , ,b, ,b, ), but no reports exist about the identification of NeuAc and GlcNAc in Xenopus testis. From our data, it could be concluded that terminal GlcNAc is more abundant than sialic acid, because labelling with GlcNAc‐binding lectins was generally stronger than labelling with NeuAc‐binding lectins.…”
Section: Discussionmentioning
confidence: 99%
“…Lectins, in combination with deglycosyolation techniques, have allowed the identification of carbohydrates in glycans of the testis of several species, mainly mammals (Arya and Vanha‐Perttula,1984,1985,1986; Craveiro and Bao,1995; Dor et al,2004; Ertl and Wrobel,1992; Kurohmaru et al,1991,1995,1996; Labate and Desantis,1995; Liguoro et al,2004; Malmi and Söderström,1987; Malmi et al,1987,1990). Some reports from our group have drawn attention to the glycan composition of amphibian testis (Sáez et al,1999,2000a,b,2001a,b,2004; Valbuena et al,2010,2011). Xenopus laevis is an animal model extensively employed in cell, molecular, and developmental biology, and so it is of interest to know their glycosidic composition.…”
Section: Introductionmentioning
confidence: 99%